Has the New Student Admission Policy Achieved Its Intended Goals? A Descriptive Analysis - Santoso, Santoso; Martak, Yusuf Faisal; Insani, Riqsal Mochamad Nur (Pusat Standar dan Kebijakan Pendidikan, BSKAP, Kemendikbudristek, 2025)
This study aims to examine whether the implementation of the New Student Admission (Penerimaan Peserta Didik Baru [PPDB]) policy promotes equitable access to quality education in Indonesia. Using National Socio-Economic Survey (Susenas, 2015–2021) data, the study assesses changes in student mobility from low socioeconomic backgrounds, transportation costs to school, and participation of students with disabilities. Schoollevel National Examination scores from 2015 to 2019 were analyzed to assess changes in the distribution of learning outcomes before and after PPDB implementation. The findings indicate that PPDB has expanded access for students from low socioeconomic backgrounds by increasing enrollment in public schools and reducing transportation costs through proximity-based admissions. Disparities in learning outcomes across schools have narrowed over time; however, this reduction is primarily attributable to declining performance in previously high-performing schools rather than significant improvements in low-performing schools. Although PPDB provides a pathway for students with disabilities to enter public schools, its effectiveness in promoting disability inclusion remains limited, as school readiness and accessibility have not improved significantly. The results suggest that PPDB contributes to greater equity in access, but its success in sustaining learning quality and inclusive education requires complementary policies targeting school capacity, teacher preparedness, and inclusive infrastructure.